Laboratory investigations on Malaysian local bentonite as a fluid loss agent in oil-well cement slurry - Samsuri, Ariffin; Junin, Radzuan; Mohamed Osman, Adil (2000)
This paper presents the result of laboratory works related to the used of Malaysian bentonite as fluid loss control agent in oil-well cement compared with the commercially used, Wyoming bentonite of USA, Lahad Datu and Tawau were Malaysian bentonite sampling areas. Treatments have been carried out to local bentonite to up grade its performance in the cement slurry. Cement sets were tested on filter press tester in two different conditions according to the API Specification 10. In addition characterization analysis and methylene blue tests were carried out for bentonite samples. From laboratory investigations, it is shown that Malaysian bentonite contains impurity materials such as quartz, feldspar, kaolinite and illite, and has CEC value lower than Wyoming bentonite. Malaysian untreated bentonite gives poor fluid loss control than Wyoming bentonite, while after treatment processes, local bentonite shows an improvement as a fluid loss control agent.